(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2019)
Every company, and often individuals, which are able to fulfill certain needs or simply just for fun, have their own internal networks as well as a simultaneous approach to the world wide web. Computers, laptops and smart mobile phones are available to all segments of society, which improves connectivity and communication. This is generally possible with the unstoppable spread of internet and unlimmited use of it`s capacities. The Internet itself offers many ways to educate users and to recognise basic and advanced computer functions. This approach is at the same time revolutionary, remarkable from the point of view of the development of human civilization that, for the first time in history, can "at one time" find all of its knowledge, experience and achievements. On the other hand, it is dangerous because there are different traps for inexperienced, and even for those who know something about protecting their privacy and finance. Most Internet users have a specific goal of doing it - correspondence with friends, finding different information, electronic commerce or electronic banking - тhe possibilities are very different and varied. Nevertheless, all those users have one thing in common, in fulfilling their goal of staying online - they do not have enough attention, time or even the will to properly protect themselves and get to know the possible troubles thay may encounter if they enter into different types of transactions or communications. It’s a fact that many classic crimes can be committed on the Internet, as well as acquiring information on users can prepare or enable the execution of almost all criminal offenses against life and physical integrity, property, copyright, and many others. In addition to them, there are also criminal offenses whose development is exclusively related to the development of electronic communication and the Internet. There is a wide range of behaviors that can be harmless, but can lead to the most serious crimes.